Aqui o meu boi vai urrar ! uma leitura espacial do bumba-meu-boi na cidade de São Luís (MA) - Carvalho, Daniel Cunha de (2009)
The bumba-meu-boi is seen as the biggest party of the popular culture of the city of St. Louis and the State of Maranhão. It is a cultural event organized and built by subaltern social subjects come from the urban periphery and / or rural town dating from at least the second century records in written sources. In the nineteenth century until the 1950s, the Bumba-meu- boi has a great process of repression perpetrated by the local elite which prohibited the presence of these manifestations in the urban area. Already in the 1960s to the present day there is a greater acceptance and interference of the ruling elite in Ludovicense bumba which shall constantly attend the urban area of São Luís This research aims to explain how the general subject of the celebrants bumba-meu-boi "found themselves" to maintain and prolong the life of the bull, the existential pathway in order to go and mark the spaces of the city of St. Louis, becoming as important an agent to the vitality of the roaring bull in the city, going in addition to (not discarding more complementing) the role of cultural commodification and the Government giving visibility to bumba. What we construct in our analysis was to emphasize the "sociability" and "commitment boiero" further enhancing the understanding of the spatial distribution of the howl of bumba put in the work of Carvalho, M. (1995) as a cultural movement that triggers the identity of celebration and spectacle. Our contribution was to identify the existence and vitality of Bumba is also give the long struggle, deceit and negotiations of subjects celebrants, both internally with other boiero, and externally with the ruling class and dominant. In general, this research traced the paths and perspectives needed to establish an understanding of the roaring bull Maranhão by the position and its history in urban space, following the paths taken by ordinary people who do bumba